KEHIDUPAN SOSIAL EKONOMI PETANI KELAPA SAWIT SETELAH TURUNNYA HARGA (Studi Kasus Sungai Guntung Kecamatan Kateman Kabupaten Indragiri Hilir) - Uswatun Hasanah; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The mayority of people in the river Guntung farming oil palm, and they choose oil palm because the process is produced faster than ordinary coconut, and depend on the economy of the oil palm plantation sector or have become the backbone for  their economy. This study aims to determine the social and economy life of oil palm farmers in Sungai Guntung Kateman District Indragiri Hiir Regency. The benefits of this research with observation, interview, and documentation techniques. This research uses purposive sampling technique used when specific informants are based on research objectives. The theory usd is the theory of social action and according to experts used namely Wolf, Soerjono Soekanto, and Abraham Maslow. This study subjects used as many as five people. The results of this study found that the many obstacles faced by oil palm farmers are the acquisition of capital for the development of oil palm farming, lack of extension program provided by the government, and constraints to the expansion of oil palm plantations, the high cost of daily staples including the cost of children’s education their children.  Keywords: Socio, Economic, Palm Oil Farmers, Social Action